S. S. ALEKSEEV AS A REFORMER OF HIGHER LEGAL EDUCATION (EUROPEAN AND ASIAN LAW REVIEW, 2024)
The article reveals the role of S. S. Alekseev in the formation and development of legal education in the country. The importance of the textbooks and manuals written by him was highly appreciated. The features of the teaching style are shown. The practice of organization and activities of the methodological seminar created by S. S. Alekseev is described. In connection with the description of the activities of S. S. Alekseev, a number of thoughts are expressed about the actual problems of modern legal education.
Keywords: Alekseev Sergey Sergeevich; legal education; textbooks and manuals; teaching style; methodological seminar; topical problems of education reform